Distributional and welfare effects of Germany's year 2000 tax reform - Richard Ochmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper empirically investigates distributional and welfare effects of Germany's year 2000 income tax reform. The reform is simulated in an ex-ante behavioral microsimulation approach. Dead weight loss of changes in capital income taxation is estimated in a structural model for household savings and asset demand applied to German survey data. Significant reductions in tax rates result in income gains for most of the households. Gains are found greater for households in higher tax brackets, whereby income inequality increases, slightly greater in East- than in West-Germany. Moreover, households increase savings and alter the structure of asset demand as a result of shifts in relative asset prices. As a consequence, utility losses reduce welfare effects for almost all households.
Keywords: C35; G11; H31; 330; Capital income taxation; household savings; asset demand; welfare effects